(untitled) (Palíndromo, 2021)
This is a study about the female body and identity in contemporary Latin American art based on performance records. Exile, territories, displacements and body are keywords for understanding the work Silueta Series (1974), composed of 200 photographs taken in a period of approximately seven years, by the cuban artist Ana Mendieta (1948-1985). Thus, this qualitative study through bibliographical survey, iconographic data collection and interpretative analysis of the collected data, taking as its starting point a historical iconographic panorama of the representation of the female body, to reflect the multiple intrinsic concepts in the artist’s work that has the female body as a central element integrated into the landscape, in addition to issues of gender, politics, identity that are subjectively established in a timeless manner. The results reveal that the poetic action of the feminine in media art can deconstruct the concepts rooted in the woman, having her own body as a support through technologies.